2013
DOI: 10.1021/ja4069968
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Opening Polymerization with Zn(C6F5)2-Based Lewis Pairs: Original and Efficient Approach to Cyclic Polyesters

Abstract: Dual systems combining Zn(C6F5)2 with an organic base (an amine or a phosphine) promote the controlled ring-opening polymerization of lactide and ε-caprolactone. The Lewis pairs cooperate to activate the monomers, affording well-defined high molecular weight cyclic polyesters. Efficient chain-extension gives access to cyclic block copolymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
146
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(156 citation statements)
references
References 47 publications
3
146
1
1
Order By: Relevance
“…30 Disappointingly, the pre-polymerization screening of compound 1 indicated no reaction between the benzyl alcohol (BnOH) and the Zn-C 6 F 5 moiety, which was also the conclusion obtained by Schnee et al and Piedra-Arroni et al when Zn(C 6 F 5 ) 2 ·toluene was employed in the presence of either BnOH or amine/phosphine 35 respectively. 13,14 In such systems, the catalyst was thought to behave as a 'monomer activator' rather than proceeding via a 'coordination insertion' pathway; the lack of activity contrasts with a …”
Section: The Compound 13-dipropoxy-p-tert-butyl-calix[4]arene (L1h 2 )mentioning
confidence: 99%
See 1 more Smart Citation
“…30 Disappointingly, the pre-polymerization screening of compound 1 indicated no reaction between the benzyl alcohol (BnOH) and the Zn-C 6 F 5 moiety, which was also the conclusion obtained by Schnee et al and Piedra-Arroni et al when Zn(C 6 F 5 ) 2 ·toluene was employed in the presence of either BnOH or amine/phosphine 35 respectively. 13,14 In such systems, the catalyst was thought to behave as a 'monomer activator' rather than proceeding via a 'coordination insertion' pathway; the lack of activity contrasts with a …”
Section: The Compound 13-dipropoxy-p-tert-butyl-calix[4]arene (L1h 2 )mentioning
confidence: 99%
“…13,14 To ensure that the polymerization would proceed through a 'coordination insertion' mechanism, the pentafluorophenyl moiety was substituted for a more nucleophilic group. To isolate a zinc alkoxide, firstly the methyl zinc derivative (compound 2) was synthesized following the literature 15 procedure.…”
Section: The Compound 13-dipropoxy-p-tert-butyl-calix[4]arene (L1h 2 )mentioning
confidence: 99%
“…To exploit the potential of NHC-ZnR2 complexes, different approaches have been followed in which the synthesis and characterization of NHC-ZnR2 are carried out, and these complexes have then been used in ROP [33]. Controlled ROP of lactide was carried out by a dual system Zn(C 6 F 5 ) 2 combined with an amine or phosphine as organic bases [34]. In this context, Bourissou and co-workers reported a dual catalytic system combining an original cationic zinc complex with a tertiary amine, which was shown to promote efficiently and in a controlled manner the ROP of lactide under mild conditions [31].…”
Section: Introductionmentioning
confidence: 99%
“…4.3 ppm suggests the absence of cyclic PLA. [12] The MALDI-TOF spectrum of the PVL (run 7, table 3, figure S26, SI) revealed a family of peaks separated by 100 Da (the molecular weight of the monomer), consistent with the presence of only oligomeric PVL. A kinetic study using 1 and 3 -5 ( figure 12) at 110 o C revealed that the polymerization rate of the ROP of δ-valerolactone exhibited a first order dependence on the δ-valerolactone concentration ( figure 12, left).…”
Section: Rop Of Rac-lactidementioning
confidence: 81%